Towards the Transatlantic Trade and Investment Partnership (TTIP) between the European Union and United States - Puślecki, Zdzisław W. (Przegląd Politologiczny, 2018)
In this research work, the author focuses on the analysis of the activity towards the Transatlantic Trade and Investment Partnership (TTIP) between the European Union and United States. It has been emphasized that the talks will reduce regulatory barriers. New agreements to remove trade barriers aim at reducing dead-weight costs and at increasing net social gains from international trade. The article examines the impact of free trade agreements like TTIP and, in particular, investor-state dispute resolution mechanisms in reducing the power of national governments to regulate and eliminate market inequality. The article offers examples of successful regulatory cooperation efforts in the hope that it will shed light on possible approaches to addressing regulatory divergences. Ideally, the best way to address problems arising from regulatory divergence would be on a multilateral basis, while taking into account the relations of the EU and the US with other countries. The main aim of the article is the presentation of the challenges for TTIP negotiations. The particular objective of the research task is the regulatory trade barriers in US-EU foreign trade policy, the nature and the promoters of TTIP, the interrelationship between regulatory standards and international cooperation in TTIP. The general theoretical approach will be of broad interest to economists interested in international questions, especially transatlantic cooperation, as well as to political scientists. The main methods applied in this research were the institutional method, comparative method, documentation method and statistical methods. Additionally, the methods of deductive and inductive forecasting were applied.